DESKRIPSI PROSES MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN REVISI TAKSONOMI BLOOM PADA SISWA KELAS VII SMP NEGERI 6 KOTABARU KALIMANTAN SELATAN - Radiatul Adawiah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2015)
The study is a qualitative study, which aims to describe the cognitive processes in solving math problem based on Bloom’s Taxonomy of Two Dimensions relating to the types of triangles at the seventh grade students of SMP Negeri 6 Kotabaru Kalimantan SelatanThe main instrument in this study is the researcher. The data were collected by giving the test, solving math problems, and interviews. Research subjects consisted of three people, who were divided into three categories namely, one higly qualified person, one moderate-ability person, and one low-ability person.The results show that (1) the cognitive process of subjects with high, medium, or low abilities in solving mathematical problems is able to indentify knowledge in long-term memory by making the triangle inside a square image; (2) both highly and medium skilled subject are able to construct a meaning that is changing the shape of the image into another form based on the given problem, while the low-ability subject is difficult in constructing meaning; (3) highly skilled subject implements or uses a procedure in certain circumstances, but not until the final answer. While the medium and low ability subject are difficult to implement or use a procedure in certain circumstances; (4) both highly and medium skilled subject are breaking down the material into its constituent parts of and determine the relationships between the parts so that the subject determines the image according to the type of triangle. While the low ability has difficulty in breaking down the material into constituent parts; (5) the high qualified subject plans a procedure to answer the problem. While the medium and low ability subjects are difficult in making hypothesis based on the criteria; (6) the high, medium, and low ability subjects are difficult in making a decision or a clear consideration in finding the cable length should be prepared with a predetermined number of triangles.   Keyword: proses penyelesaian soal matematika dan revisi taxonomy bloom